2022
DOI: 10.3389/fimmu.2022.899104
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Estrogens on Osteoimmunology: A Role in Bone Metastasis

Abstract: Bone loss associated with estrogen deficiency indicates a fundamental role of these hormones in skeletal growth and bone remodeling. In the last decades, growing recent evidence demonstrated that estrogens can also affect the immune compartment of the bone. In this review, we summarize the impacts of estrogens on bone immune cells and their consequences on bone homeostasis, metastasis settlement into the bone and tumor progression. We also addressed the role of an orphan nuclear receptor ERRalpha (“Estrogen-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 112 publications
0
2
0
Order By: Relevance
“…Additionally, a growing number of studies have shown that bone mass loss in OVX animal models is always accompanied by the abnormal accumulation of BMAT [ 11 , 40 , 41 ]. Estrogen supplementation results in an increase in bone mass and decrease in bone fat in estrogen-deficient humans and mice [ 15 , 42 ]. These results demonstrate that BMAT is associated with bone loss caused by estrogen loss.…”
Section: Postmenopausal Bone Marrow Adiposity and Fatty Acid Metaboli...mentioning
confidence: 99%
“…Additionally, a growing number of studies have shown that bone mass loss in OVX animal models is always accompanied by the abnormal accumulation of BMAT [ 11 , 40 , 41 ]. Estrogen supplementation results in an increase in bone mass and decrease in bone fat in estrogen-deficient humans and mice [ 15 , 42 ]. These results demonstrate that BMAT is associated with bone loss caused by estrogen loss.…”
Section: Postmenopausal Bone Marrow Adiposity and Fatty Acid Metaboli...mentioning
confidence: 99%
“…BC with BM frequently causes skeletal-related events. This is because breast cancer cells enter the bone marrow through interactions with endothelial cells and osteoblasts, disrupting the balance between osteoclasts and osteoblasts, affecting bone homeostasis, and subsequently leading to skeletal dysfunction, such as spinal cord compression, pathological fracture osteosclerosis, osteoporosis, osteoarthritis (7,8). As a result, patients' median survival time was reduced to 24-55 months following BM diagnosis (9,10).…”
Section: Introductionmentioning
confidence: 99%